Associations between emotional intelligence and doctor burnout, job satisfaction and patient satisfaction - Weng, Hui-Ching; Hung, Chao-Ming; Liu, Yi-Tien; Cheng, Yu-Jen; Yen, Cheng-Yo; Chang, Chi-Chang; Huang, Chih-Kun (Medical education, 2011)
Medical Education 2011: 45: 835–842 CONTEXT  The occupational health literature has long been dominated by stress‐related topics. A more contemporary perspective suggests using a positive approach in the form of a health model focused on what is right with people, such as feelings of well‐being and satisfaction. OBJECTIVES  Using a positive perspective and multi‐source data collection, this study investigated the inter‐relationships among emotional intelligence (EI), patient satisfaction, doctor burnout and job satisfaction. METHODS  In this observational study, 110 internists and 2872 out‐patients were surveyed in face‐to‐face interviews. RESULTS  Higher self‐rated EI was significantly associated with less burnout (p < 0.001) and higher job satisfaction (p < 0.001). Higher patient satisfaction was correlated with less burnout (p < 0.01). Less burnout was found to be associated with higher job satisfaction (p < 0.001). CONCLUSIONS  This study identified EI as a factor in understanding doctors’ work‐related issues. Given the multi‐dimensional nature of EI, refinement of the definition of EI and the construct validity of EI as rated by others require further examination.